2020
DOI: 10.1108/jhti-04-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

An overall assessment of sports tourism articles

Abstract: PurposeThe purpose of this study aims to examine sports tourism through a conceptual lens. The study offers a deep assessment of the general structure and purpose of sports tourism. Thus, the authors aim to determine the contributions of scientific studies in the field of sports tourism to sports tourism literature.Design/methodology/approachA qualitative research design was created and data collected using document analysis. The research articles were categorized and analyzed according to their objectives, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…[25,26] The importance of having a specialized department for public relations and not activating its role properly There is a shortcoming in the role played by public relations in containing crises. [27] The absence of an integrated strategic plan prepared in advance to confront these types of crises, as the study showed that the public relations departments in these companies lack the work of external research and preparing a crisis management team but formed committees to deal with the crisis of the January 20 revolution, and consequently, there was difficulty in providing information, which led to the inability to decide. In addition to a lack of a clear conception of the efforts that should be made when accidents occur in crises because they do not have scenarios or proposals that can be used in times of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] The importance of having a specialized department for public relations and not activating its role properly There is a shortcoming in the role played by public relations in containing crises. [27] The absence of an integrated strategic plan prepared in advance to confront these types of crises, as the study showed that the public relations departments in these companies lack the work of external research and preparing a crisis management team but formed committees to deal with the crisis of the January 20 revolution, and consequently, there was difficulty in providing information, which led to the inability to decide. In addition to a lack of a clear conception of the efforts that should be made when accidents occur in crises because they do not have scenarios or proposals that can be used in times of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling is a quantitative indicator, formed on the basis of three main approaches. In the first approach, the performance indicators of athletes are averaged in the process of competitive activity, as well as the determination of their individual characteristics [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In sports practice, the classification of models presented by A. A. Bratko, P. L. Volkov, A. N. Kochergin and G. I. Tsaregorodtsev, who subdivide all models into three types [9,15]: physical real e-models that have a similar physical, biological nature with the nature of the phenomenon under study, differing in size and speed of the phenomena (for example, in gymnastics -articulated models of gymnasts); real-mathematical -these include modeling of competitive conditions, the use of technical means; logical-mathematical -these models are abstract, they include the growth of sports achievements, the level of sports preparedness, technical skills [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…À luz do turismo esportivo, afirma-se que o evento de e-sport analisado no presente estudo trouxe, com base na amostra investigada, certa relevância para o aspecto econômico da localidade (González-García et al, 2018), já que se notou maior quantidade de turistas. Além disso, os visitantes são sujeitos importantes para o desenvolvimento do turismo esportivo (Mesci, Pekerşen & Mesci, 2021). Levando em consideração os residentes, retomam-se os apontamentos de González-García et al ( 2018) ao argumentarem que, para os residentes, esse segmento turístico provoca mais benefícios do que custos.…”
Section: Faixa Etária Dos Respondentesunclassified